Real-Time Automation in Patient Support Programs: An Event-Driven Cloud Framework for Biopharmaceutical Patient Care - Vineel Muppa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the strategic implementation of cloud technologies and Event-Driven Architecture (EDA) to revolutionize Patient Support Programs (PSPs) within the biopharmaceutical industry. The article documents how a leading biopharmaceutical company addressed critical challenges in patient enrollment, benefit verification, and medication adherence through an innovative event-driven framework. The implementation leveraged OCR-powered data extraction, AI-driven adverse event detection, sentiment analysis for personalized support, and connected monitoring devices to enable real-time interventions. Results demonstrate significant improvements in operational efficiency, reduced administrative delays, enhanced patient engagement, and strengthened regulatory compliance. The automated workflows for co-pay enrollments and financial assistance approvals particularly impacted therapy access timeframes. This case highlights how event-driven cloud solutions can transform traditional PSPs into scalable, intelligent systems that improve both patient outcomes and healthcare-provider collaboration. The article contributes valuable insights for biopharmaceutical organizations seeking to modernize patient support services through integrated technology frameworks.
Keywords: Event-Driven Architecture; Patient Support Programs; Cloud Computing; Healthcare Automation; Artificial Intelligence